Penurunan Nyeri Sendi Pada Lansia Dengan Terapi Relaksasi Autogenik Dan Terapi Guided Imagery - Sonhaji Sonhaji; Sawitry Sawitry; Selgia Siahaya (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: Elderly people face various health problems related to decreased body function, one of which is joint pain. Joint pain limits the range of motion of the elderly so that joints become stiff, have difficulty walking, and can cause disability. Joint pain causes the elderly to be unable to perform activities comfortably which results in decreased quality of life. Objectives: The Purpose to determine the effect of autogenic relaxation therapy and guided imagery therapy on joint pain in the elderly. Methods: The methods Used Quantitative Design with two group pre-test and post-test. The study used 16 respondents with a matched case-control sampling technique divided into two treatment groups with 8 respondents each. Results: The results of statistical analysis showed that there was no difference between autogenic relaxation therapy and guided imagery in the elderly with joint pain with a ρ-value of 0.558> 0.05. Conclusion: Autogenic relaxation and guided imagery are effective in reducing joint pain in the elderly.